Pengaruh kestabilan ekonomi, aliran FDI dan globalisasi terhadap trend pengangguran ASEAN-3 (Impact of economic stability, foreign direct investment flows and globalization towards unemployment trend of ASEAN-3) - Nanthakumar, Loganathan; Thirunaukarasu, Subramaniam; Mustafa, Dakian (2015)
Unemployment is one of the major challenges faced by most developing countries, especially in ASEAN. This study investigates the existence of long-run and short-run relationship between unemployment and economic stability, foreign direct investment; and economic openess. This study uses annual time series data covering the period of 1980- 2012 and employs Autoregressive Distributed Lag (ARDL) and Bayer-Hancks Combine Cointegration Test to determine the cointegration linkages between those variables. The empirical results show that economic openess have a cointegration relationship with unemployment for Malaysia, Thailand and Indonesia both in the long-run and short-run. While, the economic stability only responds to unemployment in the long-run and and short-run for Malaysia and Thailand. On the other hand, imbalance in the flows of the foreign direct investment only affects Malaysia’s unemployment. The overall findings of this study is able to guide policymakers to take into account the unemployment fluctuations faced by ASEAN-3 and establish policies to realise ASEAN Community in 2015.